Assessment of the Insolvency Risk in Companies Listed on the Bucharest Stock Exchange - Balteș, Nicolae; Pavel, Ruxandra Maria (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The present study presents, from the theoretical and pragmatic point of view, 6 of the established score models regarding the assessment of the insolvency risk, belonging to the Anglo-Saxon, Continental and Romanian schools. The research sample is made up of 26 companies belonging to the hotel industry and restaurants, listed on the Bucharest Stock Exchange. The research was carried out over a period of 11 years (2007-2017). Following the application of the score models, it was found that during the period covered by the research, a number of 14 companies had a relatively high insolvency risk and 12 of them had a relatively low insolvency risk.